1998
DOI: 10.1111/j.1749-6632.1998.tb11118.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV/SIV Enteropathy

Abstract: Evidence is increasing that HIV/SIV-induced changes in the highly differentiated gut-associated immune system play a central role in the pathogenesis of gastrointestinal manifestations in HIV/SIV infection. It has been shown in both humans infected with HIV and in nonhuman primates infected with SIV that a rapid, very early, and more pronounced loss of CD4+ T-cells occurs in the mucosa in comparison to the peripheral blood. The loss of this important regulatory T-cell subset might explain mucosal immunodeficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 42 publications
0
38
0
3
Order By: Relevance
“…Pathological findings in these macaques included severe enteritis, characterized by villus blunting, and fusion, as shown in a representative section of ileum in Fig. 1A, similar to the SIV enteropathy previously described in SIV infection (30,75,78) and are in keeping with the major impact of SIV on the GI tract (75). Opportunistic infections (OIs) were not observed in either the GI tract or other organs, suggesting that clinical disease in these animals was the direct result of SIV infection rather than secondary to immune suppression.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Pathological findings in these macaques included severe enteritis, characterized by villus blunting, and fusion, as shown in a representative section of ileum in Fig. 1A, similar to the SIV enteropathy previously described in SIV infection (30,75,78) and are in keeping with the major impact of SIV on the GI tract (75). Opportunistic infections (OIs) were not observed in either the GI tract or other organs, suggesting that clinical disease in these animals was the direct result of SIV infection rather than secondary to immune suppression.…”
Section: Resultsmentioning
confidence: 92%
“…Thus, it is not certain whether RP macaques inoculated with other SIV strains would segregate so clearly from slower progressors, as observed for SIVsmE543 and SIVsmE660 in the present study. The pathological features that we associated with rapid progression, such as MNGC formation (4), macrophage tropism (2, 17, 55), SIV enteropathy (30,43,78), and SIVE (3,61,77,81), are not unique to one specific strain of SIV. For example, previous studies of SIVmac239 and SIVsm strains have demonstrated that SIVE is highly associated with lack of SIV-specific antibody responses and a rapid disease course (3,61,77).…”
Section: Discussionmentioning
confidence: 99%
“…5 HIV/SIVassociated pathology in the GI tract includes epithelial hyperplasiainduced villous atrophy, abnormal cellular infiltrates, disrupted lymphoid architecture, and increased apoptotic cells, mostly attributed to an overt and chronic inflammatory immune response during HIV/SIV infection. [6][7][8] By contrast, SIV-infected natural nonhuman primate hosts such as sooty mangabeys (SMs) and African green monkeys do not progress to simian AIDS, unlike nonnatural hosts such as infected rhesus macaques (RMs, Macaca mulatta). 9,10 Prolonged immune activation is thought to contribute to disease progression in nonnatural hosts because natural hosts quickly dampen generalized immune activation after the acute phase of SIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…These patients often manifest clinical GI abnormalities, including nutrient malabsorption, malnutrition, diarrhea, and weight loss. 1,2 Pathologic changes in GI tissues from HIV-infected individuals include inflammatory infiltrates, villus blunting, and crypt hyperplasia. 3 A progressive loss of the CD4 ϩ T lymphocytes in the GI tract is observed early following infection.…”
Section: Introductionmentioning
confidence: 99%